A cross-sectional study on behavioural and psychological symptoms of dementia in elderly and its impact on quality of life in a tertiary care hospital - Bhagat, Gaurav; Raj, Rajnish; Sidhu, Balwant Singh; Sidhu, Amarjit Kaur (International Journal of Advances in Medicine, 2018)
Background: Historically, the word dementia was derived from Latin word ‘dementatus’, which means ‘out of one’s mind’. There were 24.3 million people with dementia in the world and 4.6 million are being added every year. Present study was done to evaluate the behavioral and psychological symptoms of dementia in elderly patients and its impact on their quality of life. Methods: It was a hospital based descriptive, cross-sectional study. 100 cognitively impaired patients in the age group of 60 years and above were enrolled. The socio-demographic profile, severity of dementia on MMSE; behavioral disturbances on BPSD; psychiatric illness on NPI; agitation on CMAI and their impact on quality of life, and disability were assessed on WHOQOL-Bref and WHO DAS 2.0 scales, respectively. Results: Out of 110 patients that were screened, 100 participated in the study (response rate 91%). Majority of subjects (53%) were illiterate and belongs to rural background (57%). Mean dementia severity score was 17.01±4.439 SD which was of mild to moderate level. Overall mean age was 68.16±8.16 SD and negatively related (r= -0.652; F=27.044, p<0.001) but weakly associated to severity of dementia. There was a statistically significant increase in the NPI scores with increase in dementia severity (Item score F=91.754, p<0.001 and distress score F=81.647, p<0.001). There was significant increase in agitation/aggression (CMAI) with an increase in severity of dementia. BPSD on NPI item score was weakly related (r=0.757) and caused increase in disability but decrease in quality of life. Dementia severity as per MMSE score was negatively related to WHO DAS disability (r= -0.863), BPSD on NPI item (r= -0.797) and agitation/aggression on CMAI (r= -0.587). WHOQOL-Bref decreases with increase in severity of dementia and disability. Conclusions: Dementia severity was of mild to moderate level and it increased with age. Most common psychiatric symptom was agitation/aggression (76%) and least common was hallucinations (12%). BPSD causes significant decrease in quality of life and an increase in severity of disability.